2020
DOI: 10.1002/ajb2.1515
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide genotyping estimates mating system parameters and paternity in the island species Tolpis succulenta

Abstract: Premise The mating system has profound consequences, not only for ecology and evolution, but also for the conservation of threatened or endangered species. Unfortunately, small populations are difficult to study owing to limits on sample size and genetic marker diversity. Here, we estimated mating system parameters in three small populations of an island plant using genomic genotyping. Although self‐incompatible (SI) species are known to often set some self‐seed, little is known about how “leaky SI” affects se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…Recent mating system estimation using field collected progeny sets from two populations on Madeira confirm predominant outcrossing (Gibson et al, 2020). However, despite a functional SI system, two of the 75 offspring scored in that study were confirmed as products of self-fertilization (Gibson et al, 2020). Crawford et al (2019) recently documented a breeding system shift from SI to SC within T. succulenta from the Azorean island of Graciosa ( Figure 2).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Recent mating system estimation using field collected progeny sets from two populations on Madeira confirm predominant outcrossing (Gibson et al, 2020). However, despite a functional SI system, two of the 75 offspring scored in that study were confirmed as products of self-fertilization (Gibson et al, 2020). Crawford et al (2019) recently documented a breeding system shift from SI to SC within T. succulenta from the Azorean island of Graciosa ( Figure 2).…”
Section: Introductionmentioning
confidence: 83%
“…Gibson et al. (2020) discuss the advantages of the methods employed herein for studying the small populations of rare island plants. A major advantage, with conservation implications, is that mating system can be inferred because individual progeny can be called as selfed or outcrossed with few maternal families and few progeny per family.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations